The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1149/1.2128121
|View full text |Cite
|
Sign up to set email alerts
|

Study of Various (“Super Iron”) MFeO[sub 4] Compounds in Li Salt Solutions as Potential Cathode Materials for Li Batteries

Abstract: In this work we studied the possibility of using Fe+6 “super iron” compounds, including BaFenormalO4,normalK2FenormalO4,CuFenormalO4 , and SrFenormalO4 as potential cathode materials for rechargeable Li batteries, and their behavior in several nonaqueous Li salt solutions. Classic electrochemical techniques, such as cyclic voltammetry and chronopotentiometry combined with X-ray photoelectron spectroscopy, X-ray diffraction, Mössbauer spectroscopy, atomic adsorption, atomic emission, in situ and ex situ at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 13 publications
6
34
0
Order By: Relevance
“…While rechargeable lithium and metal hydride anodes have increased the energy The most recent development in super-iron cathode chemistry is that it is reversible, which has led to the demonstration of rechargeable super-iron batteries. In accord with recent studies [22,24,30,32], the principal limitation to Fe(VI) reversibility has been the passivation of Fe(VI)/Fe(III) redox couple due to resistive buildup of low-conductivity ferric salts. Recently, it has been shown that ultra-thin Fe(VI) layers are reversible cathodes.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…While rechargeable lithium and metal hydride anodes have increased the energy The most recent development in super-iron cathode chemistry is that it is reversible, which has led to the demonstration of rechargeable super-iron batteries. In accord with recent studies [22,24,30,32], the principal limitation to Fe(VI) reversibility has been the passivation of Fe(VI)/Fe(III) redox couple due to resistive buildup of low-conductivity ferric salts. Recently, it has been shown that ultra-thin Fe(VI) layers are reversible cathodes.…”
Section: Introductionsupporting
confidence: 65%
“…However, the more recent evidence suggests that the iron centers undergo a partially reversible Faradaic reduction in the compounds from 6 + to 3 + states, central to this interpretation is direct Mössbauer measurement of the iron valence state of the cathode during charge storage [32]. Fig.…”
Section: Electrochemical Behavior Of Fe(vi) In Nonaqueous Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Development Reference 1999 introduction of super-iron charge storage & super-iron alkaline battery [5] 2000** introduction of super-iron lithium primary (single discharge) battery [7] 2001 demonstration of the solid state stability of the hexavalent iron [8] 1999-5 chemical syntheses of an array of super-iron salts [5,7,[9][10][11][12][13][14][15][16] 2000-4 inexpensive, electrochemical syntheses of super-iron salts [17][18][19][20][21][22][23][24][25][26] 2003-5** electrolyte optimization for super-iron lithium batteries [27,28] 2003 reversibility of alkaline, nanothick (3 nm) Fe(VI) cathodes [29] 2006 rechargeable alkaline super-iron battery [30] 2006** reversibility of non-aqueous, nanothick (3 nm) Fe(VI) cathodes [31] 2007-8 zirconia encapsulation-stabilization of alkali super-irons [32][33][34][35] 2009** rechargeable super-iron lithium battery, 4 V cathode [6] **=lithium super-iron battery development.…”
Section: Yearmentioning
confidence: 99%
“…FTIR provides not only a specific "fingerprint" distinguishing the various Fe(VI) oxides, as shown in Figure 5, but importantly we have also developed it as a quantitative technique to determine the Fe(VI) salt purity through the addition of a standardized BaSO 4 salt [8]. Discharge of cathode replaced, commercial alkaline button cells provides rapid screening of the redox activity of alternative salts [6,10,11,14,15,19,[27][28][29][30][31][32][33][34][35].…”
Section: Characterization Of Super-iron Cathode Filmsmentioning
confidence: 99%